PKM Pemberdayaan Ibu-ibu Rumah Tangga Melalui Pelatihan Limbah Bernilai Ekonomis di Rumah Kemasan Kabupaten Purwakarta - Siti Nurjanah, Riski; Saepudin, Ahmad; Jalaludin, Jalaludin (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
PKM is part of the activities of the PKK group which was pioneered by the organization that drives housewives in empowering waste as an economic asset value in Purwakarta Regency. Waste management is the most important focus for the community, which affects health and environmental hygiene. Besides being part of the discomfort in the Purwakarta environment. Waste is also exploited as part of the economic value, so that the benefits are not only from a health and hygiene aspect, but must be an economic value for the welfare of Housewives in Purwakarta. Waste management is of course the main program of the government through the waste collection program launched by the Ministry of Environment and Forestry since 2015, with the aim of reducing the amount of waste around the travel environment. This becomes very important for the PKK group to mobilize women as part of utilizing waste into economic value. The existence of these problems is interested in providing solutions by increasing the empowerment of economic value training counselling for the presence of waste in Purwakarta Regency. The stage of this research is to directly go into the field and interview the PKK organizational section and provide an analysis with references related to the handling of waste and waste as an economic value. The method of activities that will be carried out in this activity is by means of group social guidance and local community development, the techniques used are explained in the form of seminars and then training carefully. Thus, it can produce economic values in waste management in Purwakarta Regency